Anthropogenic disturbance drives dispersal syndromes, demography, and gene flow in amphibian populations. Issue 2 (9th March 2020) - Cayuela, Hugo; Besnard, Aurélien; Cote, Julien; Laporte, Martin; Bonnaire, Eric; Pichenot, Julian; Schtickzelle, Nicolas; Bellec, Arnaud; Joly, Pierre; Léna, Jean‐Paul
Abstract: There is growing evidence that anthropogenic landscapes can strongly influence the evolution of dispersal, particularly through fragmentation, and may drive organisms into an evolutionary trap by suppressing dispersal. However, the influence on dispersal evolution of anthropogenic variation in habitat patch turnover has so far been largely overlooked. In this study, we examined how human‐driven variation in patch persistence affects dispersal rates and distances, determines dispersal‐related phenotypic specialization, and drives neutral genetic structure in spatially structured populations. We addressed this issue in an amphibian, Bombina variegata, using an integrative approach combining capture–recapture modeling, demographic simulation, common garden experiments, and population genetics. B. variegata reproduces in small ponds that occur either in habitat patches that are persistent (i.e., several decades or more), located in riverine environments with negligible human activity, or in patches that are highly temporary (i.e., a few years), created by logging operations in intensively harvested woodland. Our capture–recapture models revealed that natal and breeding dispersal rates and distances were drastically higher in spatially structured populations (SSPs) in logging environments than in riverine SSPs. Population simulations additionally showed that dispersal costs and benefits drive the fate of logging SSPs, which cannot persist without dispersal. The common garden experiments revealed that toadlets reared in laboratory conditions have morphological and behavioral specialization that depends on their habitat of origin. Toadlets from logging SSPs were found to have higher boldness and exploration propensity than those from riverine SSPs, indicating transgenerationally transmitted dispersal syndromes. We also found contrasting patterns of neutral genetic diversity and gene flow in riverine and logging SSPs, with genetic diversity and effective population size considerably higher in logging than in riverine SSPs. In parallel, intrapatch inbreeding and relatedness levels were lower in logging SSPs. Controlling for the effect of genetic drift and landscape connectivity, gene flow was found to be higher in logging than in riverine SSPs. Taken together, these results indicate that anthropogenic variation in habitat patch turnover may have an effect at least as important as landscape fragmentation on dispersal evolution and the long‐term viability and genetic structure of wild populations.